Skellig - Almond, David, 1951- (New York : Delacorte Press, 1999)
Unhappy about his baby sister's illness and the chaos of moving into a dilapidated old house, Michael retreats to the garage and finds a mysterious stranger who is something like a bird and something like an angel.
"First published in Great Britain by Hodder Children's Books"--T.p. verso.
Wilson's Children.
Wilson's Junior High School.
Wilson's Senior High School.
3.5.
3.5
Keywords: Angels -- Fiction; Family life -- England -- Fiction; Moving, Household -- Fiction; Strangers -- Fiction; Angels -- Fiction; Children and strangers -- Fiction; Family life -- England -- Fiction; Moving -- Fiction; England -- Fiction; England -- Fiction